(untitled) (Journal of the College of Basic Education, 2023)
The Sultanate of Oman is an important part of the Arabian Gulf region, by virtue of its unique geographical location, as it represents the southeastern region of the Arabian Peninsula, which made it possess distinguished immunity due to the natural properties surrounding it, as it is surrounded from the north, east and west by the Arabian Gulf, the Gulf of Oman and the Arabian Sea, but from the west it is bordered by sand Which is a natural extension of the Empty Quarter desert, and thus Oman has become confined between two seas, the watery sea and the sandy sea.This geographical nature of Oman greatly affected its inhabitants, so they took to the sea and were known for being skilled navigators, and its inhabitants emerged greatly in the maritime trade between the Arabian Gulf region and between Southeast Asia, China, India and East Africa since the beginning of the eighth century AD.